HUBUNGAN ANTARA KEPERCAYAAN DIRI DENGAN KECENDERUNGAN PERILAKU AGRESIF PADA SISWA SMUN I REMBANG - Ernawati, Sri (TALENTA, 2012)
and other crime actions had been situated by teenagers. The phenomenon indicates the increase of aggressive behaviors among teenagers. The problem can no longer be considered as common mischievousness behavior, due to the negative effects. The taking place of the events could be caused by teenagerâs over-confidence. The over-convidence teenager tends to fail to judge his flaws objectively, so that he always feels that heâs perfect and better than anyone else. Â  Based on mentioned problems, researcher wants to find out the correlation between self-confidence and aggressive behavioral tendency, to answer the question whether self-confidence dos affect teenagerâs aggressive behavioral tendency. There are two variables served in this inquiry : 1) The tendency of aggressive behavior as dependent variable, and 2) self-confidence as independent variable. Â  Population in the research consists of second grade student of SMUN I Rembang. Sampling technique of the research uses Cluster Random Sampling, where all classes have the chance to be examined as research subject. There are 35 research subjects who are treated as try-out subject, and 72 research subjects who are anaysed for the research purpose. Â  In this research, the data collecting methodology used questionnaire which has already been tested its validity and reliability. The data analyzing technique uses Correlation Product Moment. Â  The result of the data analysis shows these results : there are positive correlation between self-confidence and the aggressive behavioral tendencies of the student of SMUN I Rembang. This can be seen with the rate of rxy = 0,435 with p < 0,01. Â  The level of subjectâs self confidence can be classified as high, while the subjectâs aggressive behavioral tendencies can be classified as low. The effective contribution of self confidence to aggressive behavioral tendencies is 18,9 percent. It can be concluded that there are 81,1 percent of other factors that can add contribution to affect the aggressive behavioral tendencies like temperature anf disindividuation.